Uji Efektivitas Ekstrak Kulit Batang Bakau Lindur (Bruigiera gymnorrhiza) Sebagai Antibakteri Terhadap Streptococcus pyogenes - Annisa Fath; Kurniawaty, Evi; Graharti, Risti; Berawi, Khairun Nisa (Medula, 2024)
The bacterium Streptococcus pyogenes is a gram-positive bacterium that causes various diseases in humans. Pharyngitis is the most common infection caused by Streptococcus pyogenes, occurring in 15-30% of children and 5-10% of adults. The extract of mangrove bark contains bioactive compounds that can serve as an antibacterial alternative.  This research is an experimental study. The mangrove bark was extracted using 96% ethanol solvent through the maceration method and subjected to phytochemical testing. The treatment consists of 96% ethanol extract preparations with concentrations of 25%; 50%; 70%; 90%; and 100%, as well as a negative control using aquades and a positive control using amoxicillin. Each treatment was repeated 4 times. Antibacterial activity testing was conducted using the well method on Muller Hinton Agar. The results of the phytochemical test showed that the 96% ethanol extract positively contained flavonoid, phenol, alkaloid, tannin, saponin, steroid, and triterpenoid compounds. The results of the antibacterial activity study from 25%, 50%, 70%, 90%, and 100% concentrations of 96% ethanol extract produced zone diameters of 4.33 mm; 5.68 mm; 6.61 mm; 7.72 mm; and 9.02 mm. These results indicate that the 96% ethanol extract of the mangrove bark has an inhibitory effect on the growth of Streptococcus pyogenes. Data analysis of the 96% ethanol extract of the mangrove bark using the One-Way ANOVA test showed p< 0.05.